Innovation in the Smart City Concepts – Theoretical Framework, Solution and Research Fields - Blanka TUNDYS; Konrad Henryk BACHANEK; Ewa PUZIO (Communications of International Proceedings, 2020)
The main task of smart cities is to strive for sustainable development in such a way as to meet the needs of the present generation without compromising the living conditions of future generations. The limited resources and the need to maintain or increase the quality of the services offered at the same time as various problems arise, require the use of solutions, including innovative technologies and concepts, which by definition fall within the scope of smart city. The aim of the article is to discuss theoretical aspects related to the construction of smart city concepts, including an in-depth bibliometric analysis related to the topic, as well as to indicate the scope and areas of the innovations in the implemented concepts. The authors will define the concept of smart city, elements, dimensions and areas included in the main assumptions of the concept. Special attention will be paid to the aspect of sustainability and "green" practices taken in cities. In this paper will be show what areas are of interest to researchers, how popular this area of research is, what are the links between authors and to what extent articles on this topic are cited. Authors present the own taxonomy relating to the classification and assignment of the smart city concept to particular fields of science  and to refer innovative solutions implemented in the smart city concepts.
Keywords: Bibliometric analysis; smart city; innovation.